Family Life – between Charism and Institution. Signalling Multidimensionality and Complexity of Human Interactions for Business Institutions and Society - Michalski, Michał (Annales. Etyka w Życiu Gospodarczym, 2014)
This paper analyses the complexity of family life, which includes both its charismatic and institutional aspects. Deepening the understanding of this basic social group can be useful in explaining how human beings in their decisions and actions, as well as organizations, unceasingly transcend different oppositions and dimensions. Undertaking this topic is not only important in the context of understanding the fundamental and complex experience of family life in the process of preparing and introducing new members to society, but also from the organizational perspective. It means that exploring the role of both dimensions – charismatic and institutional – which are somehow complementary, is crucial for understanding and harmonizing the different relationships and interactions within organizations, including business ones. In this way the article shows the connection between the functioning of the family and society (including organizations within it).